2021
DOI: 10.1080/21655979.2021.1988251
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antibiotic-induced drug resistance of Salmonella enteritidis and its biofilm formation mechanism

Abstract: This research was to explore the antibiotic-induced drug resistance of Salmonella enteritidis and its biofilm formation mechanism. Kirby-Bauer (K-B) disk method recommended by Clinical and Laboratory Standards Institute (CLSI) was used to test the drug sensitivity of Salmonella enteritidis to 16 kinds of antibiotics including ß-lactams, aminoglycosides, quinolones, sulfonamides, chloramphenicols, and tetracyclines. Polymerase chain reaction (PCR) was performed to detect the carrying of drug resistance genes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…These previous results are consistent with our findings, showed that antimicrobial resistance may correlate with biofilm formation. Biofilm formation will enhance resistance to antibiotics and disinfectants, enhance the ability of Salmonella to survive in animals and the environment, leading to big harm to animals ( Dai et al, 2021 ). This study underlined the ability of Salmonella to contaminate food possibly attributed by their biofilm producing capability.…”
Section: Discussionmentioning
confidence: 99%
“…These previous results are consistent with our findings, showed that antimicrobial resistance may correlate with biofilm formation. Biofilm formation will enhance resistance to antibiotics and disinfectants, enhance the ability of Salmonella to survive in animals and the environment, leading to big harm to animals ( Dai et al, 2021 ). This study underlined the ability of Salmonella to contaminate food possibly attributed by their biofilm producing capability.…”
Section: Discussionmentioning
confidence: 99%
“…Enteritidis was resistant to nalidixic acid (94.5%), ampicillin (75%), streptomycin (67%), cefoperazone (52%), and sensitive to cephalosporin and ciprofloxacin. 5 Cephalosporins and ciprofloxacin are the first-line drugs for treating Salmonella infections, with azithromycin as an adjuvant treatment. However, as the sensitivity of Salmonella to cephalosporins and ciprofloxacin gradually decreases, strains that are resistant to both cephalosporins, ciprofloxacin, and azithromycin have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…is a naturally occurring phenomenon, which can be exacerbated by selection pressures stemming from the overuse of antibiotics in medical and livestock breeding practices [ 35 ]. In our study, the top five most frequently observed resistant antimicrobials were tetracycline (49.1%), ampicillin (48.2%), streptomycin (35.1%), trimethoprim/sulfamethoxazole (30.7%), and nalidixic acid (28.1%), all of which are commonly used in clinical treatments [ 36 ]. Moreover, historically, tetracycline and streptomycin have been widely employed as growth promoters in animal husbandry [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%